Adherence to treatment in patients undergoing dialysis - V., Rakshitha B.; G. K., Nalini; G. N., Sahana; P., Deepak; Nagaral, Jayashree V.; N., Mohith; C. R., Divyashree (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chronic Kidney Disease (CKD) is a silent disease that is frequently diagnosed in advanced stages. The prevalence and incidence of chronic kidney disease (end-stage renal disease) are continuously increasing, particularly in elderly patients. Poor adherence to complex multimodal therapies is a widely recognized problem in the daily care of dialysis patients, contributing to excess morbidity and mortality of this population. Aims and objectives was to assess the adherence to medications among patients undergoing haemodialysis and to explore the factors affecting non adherence. Methods: After obtaining approval from Institutional Ethics Committee, a prospective observational study was carried out among 150 patients, who were on dialysis in a tertiary care hospital, Hassan. An eight item Morisky Medication adherence questionnaire was used to assess medication adherence. Chi-square test applied to assess statistics. Results: Adherence levels were 28%, 42% and 30% for high, medium and poor adherence respectively. The overall prevalence of non-adherence among respondents was 30%. Among them 77.77% were males, 44.44% belonged to age group of 41-60 years, 40% illiterate, 60% employed, 51.11% of patients with smoking and alcoholic habits were not adherent to Dialysis. Other reasons contributing to non-adherence to treatment were forget fullness (86.66%), inadequate knowledge about side effects (80%), unhappy clinical visits (71.11%) and lack of assistance (48.88%). Conclusions: In this study patient showed moderate adherence. This emphasizes the need for constant motivation and education at frequent intervals to ensure better adherence.